Internationalization of Portuguese startups: The process and influential factors - Aragão, André Castillo Espírito Santo (2019)
As part of the Master of Science in Management, this thesis approaches the topic of internationalization applied to portuguese startups, to whom internationalization has become highly common over the last decades, either due to the drive to grow, or the need to survive. Consequence of the limited dimension of the Portuguese market and the homogenization of the global markets, internationalization became a strategy that startups seek from the early beginning. Studying about the internationalization process of portuguese startups and its influential factors allows us to understand and gather good practices, in order to create knowledge to improve the internationalization process of startups, which might want to take the international path. To accomplish the above described, a theoretical framework on international business was provided, followed by the analysis of three portuguese startups that have undertaken internationalization. In general terms, it was concluded that it is not possible to look at the internationalization process of portuguese startups as a linear phenomenon explained by one single model. Even though some particularities are mutually exclusive, these models are evolutions of each other and, most importantly, explain internationalization from different perspectives, which makes them in a way complementary. Although none of the models explains all three case studies, a pattern of the internationalization process of portuguese startups was found, beginning with direct exports and followed by the enrolment in strategic alliances. The research also highlighted several influential factors to the process, such as market knowledge, company’s network, physic distance and technological innovation.